SIMULATION OF THE TECHNIQUE OF PEDALING OF CYCLISTS ON THE BASIS OF VISUAL CONTROL OF THE CORRESPONDENCE OF THE RHYTHM OF ANGULAR MOVEMENTS IN THE LINKS OF A KINEMATIC CHAIN - Chermit, K.D.; Zabolotny, A.G.; Tikhonov, I.V.; Al Mahdi Shawkat Ezzat Abdullah (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the possibility of correcting the movements of the links of the kinematic chain of the motor apparatus of cyclists when performing the technique of circular pedaling based on visual control over the compliance of the realized movement with the ideal model of the power graph. Methods and structure of the study. The work was carried out in the laboratory of ergonomic biomechanics of the Adyghe State University, 19 cyclists of the first category and CMS took part. Athletes were asked to demonstrate the technique of circular pedaling on the WATTBIKE bicycle ergometer, which allows real-time visualization of the power graph. At the same time, based on the results of visual control of the power graph, the athlete can make corrections to the technique of the performed action and control its quality. Results and conclusions. The stability of the manifestation of the rhythm of angular movements in the knee and hip joints is manifested in all methods of pedaling and is typical for all subjects. When pedaling in accordance with the visual comparison of one’s own movements with the power graph model, the rhythm of angular movements in the knee and hip joints increases due to a decrease in the time spent on the implementation of one cycle of pedal rotation, as well as a decrease in the magnitude of angular movements in the knee and hip joints, correction of rhythmic structures of implementation of angular movements in the ankle joint and in the best athletes - correction of the spatial structure of the rhythm.